Earth Observation Open Science and Innovation - Mathieu, Pierre-Philippe; Aubrecht, Christoph (ISSI Scientific Report Series, 2018)
geospatial analytics; social observatory; big earth data; open data; citizen science; open innovation; earth system science; crowdsourced geospatial data; citizen science; science in society; data science